Determinants of In-Court Settlements: Empirical Evidence from a German Trial Court - Michael Berlemann; Robin Christmann (Verein für Socialpolitik, Ausschuss für Wirtschaftssysteme und Institutionenökonomik, 2016)
Because verdicts are typically the more costly resolution of legal disputes, most governments are interested in high settlement rates. In this paper, we use a unique dataset of 860 case records from a German trial court to explore which factors have a significant impact on the decision to settle in civil law litigation. We find that case-specific factors, procedural aspects and individual characteristics of the involved judge have a significant impact on settlement probability. Interestingly, we find supporting evidence for the hypothesis that the gender of the involved judge has an impact on settlement probabilities in certain subfields of law. Based on our empirical results, we derive some conclusions for legal policies that aim at increasing settlement rates.
Keywords: K10; K41; C78; J16; 330; settlement rate; judge; mediation; bargaining; procedural rules; gender effects